Research on the Talent Training Mode of School-enterprise Deep Integration and Process Education Philosophy - Zhou, Cong (European Journal for Philosophy of Religion, 2022)
In 2013, the proposal of China's "the Belt and Road" policy marked the birth of a new stage of international talent training. Under this macro background, the training goal of business and enterprise management professionals in China's colleges should be oriented to high-tech application-oriented talents working in the front line, which is consistent with the demand of the international vision of building the "the Belt and Road". In addition, the construction of the "the Belt and Road" infrastructure also requires the service and support of colleges at the level of school enterprise integration. This manuscript takes the data mining algorithm as the starting point to deeply explore the purpose and training mode of the quality evaluation of the integration of industry and education under the background of the "the Belt and Road" and obtain a quantitative model. From the results of dynamic clustering experiments, it can be seen that when the three categories are clustered, the first category of sample A is the "school enterprise integrated talent training environment" with high scores, of which samples 2 and 6 are more similar. The second type of sample B is that the evaluation score of "school enterprise integration and cooperation effect" is slightly lower while the evaluation score of "school enterprise integration and cooperation process" is higher, and the fitting degree of samples 3 and 8 is better. The evaluation scores of the three types of sample C are "school enterprise integration enterprise quality" and "school enterprise integration cooperation effect", while the deviation degree of F value of 7 and 9 is smaller. Through cluster analysis and data fitting of different samples, it provides a new method and new idea for constructing a quantitative, whole process, multi-level and multi-level quality evaluation model of school enterprise integration of industrial and commercial enterprise management specialty in colleges.